MEASURING THE RESILIENCY OF HYBRID PROJECTS AGAINST SUPPLY CHAIN DISRUPTIONS - Hamad, Mustafa (My University, 2018)
The construction industry has unique supply chain relationships given the fact it is project based. As a result, the collaboration in supply chain relationships face a variety of problems that affect one or more of the project objectives: time, cost, quality, scope, or safety. Many uncertainties exist in the prefabrication supply chain as a result of which the on-site activities have to stop and wait. These uncertainties are the basis for many failures and misunderstandings that occur during construction, resulting in high failure costs due to rework and time delay. It is a challenge for the risk managers to ascertain the potential uncertainties and manage the operational disruption risk in the prefabrication supply chain of a construction project. Therefore, risk managers may employ countermeasures that leave their project or company exposed to significant risks. The goal of this research study is to examine the resiliency of hybrid projects against supply chain disruption by investigating the disruption risk exposure inherited from uncertainties in the prefabrication supply chain. A model capable of evaluating and measuring the impact of a disruption originating anywhere in the supply chain was developed and implemented to test its usability in front-end planning of hybrid construction projects. The test demonstrated that the application of this model exposed significant uncertainties found in the prefabrication process, and that the model provided valuable information to risk managers on the operational disruption risk allowing them to make informed decisions and allocate resources more judiciously.
Keywords: construction; construction supply chain; off-site construction; Prefabrication; supply chain disruption; hybrid construction; risk management; disruption risk; off-site construction logistics